Aii810, a Novel Cold-Adapted N-Acylhomoserine Lactonase Discovered in a Metagenome, Can Strongly Attenuate Pseudomonas aeruginosa Virulence Factors and Biofilm Formation - Fan, Xinjiong; Liang, Mingjun; Wang, Lei; Chen, Ruo; Li, He; Liu, Xiaolong (Frontiers in Microbiology, 2017)
The pathogen Pseudomonas aeruginosa uses quorum sensing (QS) to control virulence and biofilm formation. Enzymatic disruption of quorum sensing is a promising anti-infection therapeutic strategy that does not rely on antibiotics. Here, a novel gene (aii810) encoding an N-acylhomoserine lactonase was isolated from the Mao-tofu metagenome for the first time. Aii810 encoded a protein of 269 amino acids and was expressed in Escherichia coli BL21 (DE3) in soluble form. It showed the highest activity at 20 ˚С, and it maintained 76.5% of activity at 0 ˚С and more than 50% activity at 0–40 ˚С. The optimal pH was 8.0. It was stable in both neutral and slightly alkaline conditions and at temperatures below 40 ˚С. The enzyme hydrolyzed several ρ-nitrophenyl esters, but its best substrate was ρ-nitrophenyl acetate. Its kcat and Km values were 347.7 S−1 and 205.1 μM, respectively. It efficiently degraded N-butyryl-L-homoserine lactone and N-(3-oxododecanoyl)-L-homoserine lactone, exceeding hydrolysis rates of 72.3% and 100%, respectively. Moreover, Aii810 strongly attenuated P. aeruginosa virulence and biofilm formation. This enzyme with high anti-QS activity was the most cold-adapted N-acylhomoserine lactonase reported, which makes it an attractive enzyme for use as a therapeutic agent against P. aeruginosa infection.